2018
DOI: 10.1002/ps.4871
|View full text |Cite
|
Sign up to set email alerts
|

Large reductions in pesticides made possible by use of an insect‐trapping lamp: a case study in a winter wheat‐summer maize rotation system

Abstract: If pesticides are used in a timely fashion and at the appropriate stage, their use may be greatly reduced with the help of an insect-trapping lamp. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The results showed that reducing chemical fertilizer significantly improved the NUE, reduced N leaching (23.7%) and improved the N economic benefit (NEB, 41.8%) as compared to the conventional fertilizer. Guo et al [28] found that when pesticides are reduced by 35-65%, it had no adverse effect on crop yields and thus had the potential to reduce the costs of pest control and produce the greatest economic benefit. Lechenet et al [29] stated that the reduction of pesticide use was one of the critical drivers to preserve the environment and human health.…”
Section: Positive Effects Resulting From Reducing Agrochemical Inputsmentioning
confidence: 99%
“…The results showed that reducing chemical fertilizer significantly improved the NUE, reduced N leaching (23.7%) and improved the N economic benefit (NEB, 41.8%) as compared to the conventional fertilizer. Guo et al [28] found that when pesticides are reduced by 35-65%, it had no adverse effect on crop yields and thus had the potential to reduce the costs of pest control and produce the greatest economic benefit. Lechenet et al [29] stated that the reduction of pesticide use was one of the critical drivers to preserve the environment and human health.…”
Section: Positive Effects Resulting From Reducing Agrochemical Inputsmentioning
confidence: 99%
“…Fertigrain Foliar, a leaf biostimulant that facilitates the vegetative development of plants; promotes better grain ripening; increases ear-grain content; builds stress resistance; improves productivity and yielding capacity; eliminates micronutrient deficiencies. The composition is 5% nitrogen, 40% organic matter, 0.75% zinc, 0.5% manganese, 0.1% copper, 0.1% boron, 0.1% iron, 0.02% molybdenum, 0.01 % cobalt, 8% free L amino acids (dose in the experiment -1 l/t) (3,(17)(18)(19).…”
Section: Methodsmentioning
confidence: 99%
“…From an internal perspective, most studies have empirically explored the influence of farmers’ risk perceptions, subjective norms, and their perceived values on safe pesticide use based on the farmers’ behavioral theory [ 12 ], planned behavior theory [ 13 ], and health belief theory [ 14 ]. From an external viewpoint, numerous scholars find that external factors, such as information access [ 15 ], external risk [ 12 ], technological environment [ 16 ], differentiated policies [ 17 ], skills training [ 18 ], and the economic environment, also play an increasing role in influencing pesticide safety use [ 18 , 19 ]. However, significant differences between farmers’ perceptions of safety behavior and actual behavior status [ 20 ] make the factors influencing farmers’ safety production gradually become more abundant; for example, Guo et al (2021) conducted a study about rice farmers’ safe production and found that farmers’ behavior resulted from a combination of internal and external factors.…”
Section: Introductionmentioning
confidence: 99%